Reducing the Risk of Decubitus in the Elderly with Back Massage Therapy using VCO (Virgin Coconut Oil) - Agnia, Winda; Kartilah, Tetet (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Elderly people experience a natural decline in body function (aging process) over a long period of time. One of the problems that can occur in the elderly is pressure sores. The worldwide incidence of decubitus ulcers ranges from 1 to 56, with 60 to 90% occurring in people over 65 years of age. Skin care to prevent pressure sores is a back massage using VCO (Virgin Coconut Oil) as a moisturizer. Purpose: This study aimed to determine the effect of VCO (Virgin Coconut Oil) back massage therapy on the risk of pressure sores in the elderly at the Welas Asih Home, Tasikmalaya Regency. Method: The research design used was a quasi-experimental one-group pretest and posttest using quantitative methods. This study used the Braden Scale to measure the risk of pressure ulcers in respondents. The sample for this study consisted of 18 elderly people from Panti Welas Asih who met the inclusion criteria. This test was carried out twice a day for four consecutive days, from 3 May to 8 May 2023. An analysis was performed to determine the impact of this research using a paired sample t-test. Results: obtained p-value = 0.000 < α. α value = 0.05. Conclusion: Back massage therapy with VCO is effective in preventing the risk of pressure ulcers in the elderly at Panti Welas Asih.